2010
DOI: 10.1177/1934578x1000500109
|View full text |Cite
|
Sign up to set email alerts
|

A New Alkaloid and Flavonoids from the Aerial Parts of Euphorbia guyoniana

Abstract: One novel alkaloid, 1,5-diphenyl-3-styryl-2-pyrazoline 1, in addition with six known flavonoids namely, kaempferol, kaempferol 3-O-glucoside, kaempferol 3-rutinoside, quercetin, quercetin 3-O-glucoside, and rutin, were isolated from the aerial parts of Euphorbia guyoniana. Their structures were established on the basis of physical and spectroscopic analysis, and by comparison with the literature data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…[38][39][40][41] Alkaloid 7 (1,5-diphenyl-3-styryl-2-pyrazoline) was isolated from aerial parts of Euphorbia guyoniana. 42 We have adopted TfOH mediated electrocyclization to access alkaloid 7 starting from cinnamaldehyde 1n, phenylhydrazine 2a and styrene 3. In this reaction, the formation of pyrazole 8 via intramolecular electrocyclization is expected to compete with the formation of the desired alkaloid 7 via intermolecular electrocyclization (Scheme 3).…”
mentioning
confidence: 99%
“…[38][39][40][41] Alkaloid 7 (1,5-diphenyl-3-styryl-2-pyrazoline) was isolated from aerial parts of Euphorbia guyoniana. 42 We have adopted TfOH mediated electrocyclization to access alkaloid 7 starting from cinnamaldehyde 1n, phenylhydrazine 2a and styrene 3. In this reaction, the formation of pyrazole 8 via intramolecular electrocyclization is expected to compete with the formation of the desired alkaloid 7 via intermolecular electrocyclization (Scheme 3).…”
mentioning
confidence: 99%
“…Ferulic acid is a phenolic compound that was identified from Euphorbia tirucalli (De Araújo 2014 ). Boudiar et al ( 2010 ) identified six known flavonoids namely, kaempferol, kaempferol 3- O -glucoside, kaempferol 3-rutinoside, quercetin, quercetin 3- O -glucoside, and rutin from the aerial parts of Euphorbia guyoniana . This suggests that E. golondrina might contain compounds that scavenge and this may account for the regulation of pathological conditions induced by nitric oxide and its oxidation product, peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…The ruthenium(II)-catalyzed oxidative C-N coupling of 2,4-dinitrophenylhydrazone of (1E,4E)-1,5-diphenylpenta-1,4-dien-3-one 50 in the presence of oxygen (1 atm) as the oxidant, afforded (E)-1-(2,4-dinitrophenyl)-5-phenyl-3-styryl-1H-pyrazole (48). [RuCl 2 (p-cymene)] 2 (5 mol%) was found to be the best catalyst for this oxidative C(sp 2 )−H amination (Scheme 12) [73].…”
Section: Intramolecular Oxidative C-n Coupling Of Hydrazonesmentioning
confidence: 99%
“…Although pyrazoles are rare in nature, due to the difficulty of living organisms to construct the N–N bond [ 46 , 47 ], a styrylpyrazole natural derivative, ( E )-1,5-diphenyl-3-styryl-2-pyrazoline (DSDP) 15 (also known as ( E )-1,5-diphenyl-3-styryl-4,5-dihydro-1 H -pyrazole) ( Figure 6 ), was isolated from the aerial parts of Euphorbia guyoniana [ 48 ]. In 2017, Kundu et al unveiled the binding interaction of DSDP 15 with the calf thymus DNA (ctDNA) [ 49 ].…”
Section: Properties Of Styrylpyrazolesmentioning
confidence: 99%